Vigilant things : on thieves, Yoruba anti-aesthetics, and the strange fates of ordinary objects in Nigeria - Doris, David Todd (University of Washington Press, 2011)
"Throughout southwestern Nigeria, Yoruba men and women create objects called ààlé to protect their properties from the ravages of thieves. Ààlé are objects of such unassuming appearance that a non-Yoruba viewer might not register their important presence in the Yoruba visual landscape. David T. Doris argues that ààlé are keys to understanding how images function in Yoruba social and cultural life"--Publisher description